SURVIVAL STRATEGIES OF PASAR SAMBAS COSMETICS TRADERS IN THE DIGITAL ERA - Rahayu, Putri; Br. Sinuhaji, Suci Ratu Carissa; Tanjung, Nurbaiti; Fitriani, Rewi (PERSPEKTIF: Journal of Social and Library Science, 2024)
This research aims to analyze the impact of the development of the digital era on cosmetics traders in the Pasar Traditional Sambas Medan, the survival strategies applied by these traders, and how these strategies are seen from an Islamic economic perspective. This research uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that the digital era had a significant impact on traditional traders, especially in the form of a decrease in the number of buyers which resulted in a decrease in income. To survive, cosmetics traders in the Pasar Traditional Sambas Medan apply various strategies, such as following product trends, providing discounts, maintaining the quality of goods, expanding social networks with buyers, and improving service quality. In addition, Muslim traders also integrate Islamic economic principles, such as tawhid, honesty, responsibility, and justice, in their survival strategies amid the challenges of the digital era.